Evaluation of Dose Calculation Algorithms of Isogray Treatment Planning System Using Measurement in Heterogeneous Phantom - Mostaar, Ahmad; Golestani, Asiyeh; Houshyari, Mohammad; Jabbari Arfaie, Ali (Reports of Radiotherapy and Oncology, 2015)
Background: Radiotherapy is a high-energy ionizing radiation treatment for some kinds of cancers. Accuracy and the quality of radiotherapy treatment planning systems depend on the type of dose calculation algorithms that are utilized. There are uncertainties in the calculation of dose distribution, especially in a heterogeneous situation. Objectives: This study calculated and compared dose with model-based algorithms (superposition, collapsed cone convolution (CCC) and fast Fourier transform (FFT) and a measure-based algorithm (Clarkson in two modes: heterogeneity active and inactive). Materials and Methods: A heterogeneous phantom was used based on a semi-anthropomorphic phantom CIRS thorax 002 LFC. All of the tests were planned according to IAEA TEC-DOC 1583. All measurements were performed with a 6 MV photon beam of a linear accelerator (ELEKTA Compact) and Farmer ionization chamber. Five methods were utilized to calculate dose and were compared with measurement results as the gold standard. Results: In the homogeneity media all algorithms had good accuracy and dose difference was below 3%, but in the inhomogeneity situation dose difference increased and in some cases did not achieve agreement criteria. The Superposition algorithm overall has minimum deviations in all cases. However in some cases CCC had better accuracy. The Clarkson algorithm had maximum differences, especially when inhomogeneity correction was inactive. Conclusions: Dose calculation algorithms applied in radiotherapy treatment planning systems have different accuracy. Model-based algorithms have a better accuracy over measurement-based algorithms such as Clarkson. In the presence of large inhomogeneity, it is strongly recommended to activate manual inhomogeneity correction.